Comprehensive Review of Antihypertensive Therapy: Pathophysiology, Diagnosis, and Management - Yuar, Alana Akmal (Jurnal Biologi Tropis, 2025)
Hypertension is fundamentally defined as a medical condition characterized by persistent elevations in systemic blood pressure. Various approaches to address hypertension include pharmacological and non-pharmacological therapies. This literature review aims to comprehensively review antihypertensive therapy: pathophysiology, diagnosis, and management. This article was compiled using a literature review method and developed using the PRISMA approach. The findings indicate that hypertension therapy can be carried out in two ways: pharmacological and non-pharmacological. Non-pharmacological therapy through lifestyle interventions is not only effective in lowering blood pressure but also provides overall health benefits. The main components of non-pharmacological interventions include dietary modification, physical activity, weight management, and cessation of detrimental habits such as smoking and excessive alcohol consumption. Pharmacological therapy is based on two main factors: blood pressure levels and the patient's total cardiovascular risk profile. Modern treatment strategies strongly recommend the use of combination therapy as an initial step in most patients. The recommended combination is a renin-angiotensin system (RAS) blocker (ACE inhibitor or ARB) with a calcium channel blocker (CCB) or a diuretic. A new and emerging pharmacological approach is more comprehensive RAAS inhibition. In conclusion, hypertension therapy can be carried out in 2 ways, namely non-pharmacological therapy and pharmacological therapy.